Caracterização da produção de biofilme por isolados de Aspergillus spp. e o seu impacto biológico - Trindade, Mario Roberto de Sousa [UNIFESP] (2017)
In the last decade, the biomedical literature has described that Aspergillus spp. isolates are able to grow adhered to biotic and abiotic surfaces, surrounded by a polysaccharide extracellular matrix that provides protection from physical and chemical agents, such as the immune system and antifungal drugs. This study aims to characterize the biofilm formation by 18 isolates of Aspergillus section Flavi and section Fumigati, also to evaluate its impact in the antifungal susceptibility “in vitro” and in the virulence. The identification of Aspergillus spp. isolates was realized through a polyphasic approach, including phenotypic tests and molecular identification. The in vitro susceptibility profile was evaluated using the broth microdilution method (CLSI, document M38-A2). The biofilm formed by isolates of Aspergillus spp. was quantified using the crystal violet technique and the impact of this biofilm in the antifungals activity was evaluated by the XTT tetrazolium salt. Isolates with higher biofilm formation capacity were selected for micromorphological characterization by confocal microscopy before and after treatment with amphotericin B and voriconazole. The virulence of the strains with higher and lower biofilm formation capacity were evaluated using the experimental model of infection in Galleria mellonella, generating a survival curve. The identification using a polyphasic approach, allowed the accurate identification of all 18 isolates, namely: six A. tamarii, six A. flavus and six A. fumigatus. All isolates presented MIC values against the antifungals tested in accordance to data described in the literature. The A. fumigatus isolates produced more biofilm than A. tamarii and A. Flavus isolates, with no difference between the later two. Biofilm cells from all isolates of Aspergillus spp. were resistant to triazoles and presented varied susceptibility to amphoterin B. The confocal microscopy analyses demonstrated that the biofilm is composed of well delineated and metabolically active hyphae, however, this aspect was greatly altered after exposure to antifungals. Using the G. mellonella invertebrate model, we observed that all isolates were capable of 100% mortality, in 24 hours for invertebrates infected with A. tamarii and A. flavus and in 96 hours for invertebrates infected with A. fumigatus. The high biofilm-forming phenotype did not affect the survival of the invertebrates Our results demonstrate that the antifungals tested have some level of action on the biofilm formed by Aspergillus spp. even at concentrations lower than the MIC value for these isolates. It was not possible to establish a relationship between the biofilm formation capacity and the survival time.